A STYLISTIC ANALYSIS OF PERSUASIONIN WONDERFUL INDONESIA’S ADVERTISEMENT - Aang Fatihul Islam; Dian Anik Cahyani (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2016)
Widely language is interconnected, language, for example, as a means of expression in advertising. Wonderful Indonesia conducted with the aim to analyze the linguistic aspects of the narrator's danger style in persuading from the public or the public about the greatness of Indonesia. The main purpose of this research is to remove the kind of language style features including lexical patterns and lexicon-syntax options that can be metaphorical and prosodic features in the movements of audiences or listeners that are implemented in the advertising of Wonderful Indonesia choice. This research uses a content analysis research design with stilistika approach. The findings show the narrator in the advertisement Wonderful Indonesia applies two types of stylistics with lexical patterns that become: repetition, parallelism, and numbers. The second type is the lexico-syntactic option (figurative language) which is: antithesis and personification.